Spirituality in Urban Architecture: a Study of Symbolism in Yogyakarta’s Urban Landscape - Wibisono, Ario; Huringiin, Nabila (Sinektika: Jurnal Arsitektur, 2026)
The development of modern cities over the past few decades tends to overlook the spiritual and symbolic dimensions in urban space design, including in Yogyakarta, which is rich in cultural heritage and spatial philosophy. Rapid urbanization and commercial development have the potential to shift the function of sacred spaces into business and tourism areas, threatening the preservation of spiritual values that form the city’s cultural identity. This study aims to investigate how traditional spiritual values and symbolism persist and transform within the dynamics of contemporary urban spaces in Yogyakarta, as well as to provide recommendations for integrating cultural and spiritual values into future urban planning. An exploratory qualitative approach was employed, focusing on symbolic areas such as the Keraton, Alun-Alun, Tugu Jogja, Malioboro, and Taman Sari. Data were collected through field observations, in-depth interviews with cultural experts, architects, and community leaders, as well as visual documentation. The analysis utilized semiotic and spatial methods to map the relationships between symbols, space, and spiritual meanings. The results indicate that Yogyakarta’s landscape structure still preserves strong spiritual values, such as the philosophical axis of Merapi–Keraton–Parangtritis and sacred buildings serving as centers for ritual and social activities. However, urbanization and modernization have led to a shift in spatial functions toward economic orientation, eroding the meanings and community connections with their cultural heritage. The recommendations emphasize the necessity of integrating cultural and spiritual values into spatial planning policies through the preservation of symbolic structures and the adaptation of local design principles. Additionally, strengthening community and indigenous stakeholder participation is crucial to ensure the continued transmission of spiritual values. This approach is expected to foster the development of cities that are not only functional but also socially and spiritually meaningful.